2023
DOI: 10.1039/d2md00378c
|View full text |Cite
|
Sign up to set email alerts
|

The war on hTG2: warhead optimization in small molecule human tissue transglutaminase inhibitors

Abstract: Human tissue transglutaminase (hTG2) is a multifunctional enzyme with protein cross-linking and G-protein activity, both of which have been implicated in the progression of diseases such as fibrosis and cancer...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…13,14 Instead, they have better lent themselves as functional cysteine-reactive probes. 15,16 The less reactive chlorofluoroacetamide has also been explored as a more stable alternative warhead 17,18 although the addition of fluorine may prove to be detrimental to binding affinity. 18 Despite these challenges, the α-chloroacetamide derivatives remain of particular interest and are still included in screening campaigns along with their acrylamide counterparts where, in some cases, they prove to be superior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Instead, they have better lent themselves as functional cysteine-reactive probes. 15,16 The less reactive chlorofluoroacetamide has also been explored as a more stable alternative warhead 17,18 although the addition of fluorine may prove to be detrimental to binding affinity. 18 Despite these challenges, the α-chloroacetamide derivatives remain of particular interest and are still included in screening campaigns along with their acrylamide counterparts where, in some cases, they prove to be superior.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The less reactive chlorofluoroacetamide has also been explored as a more stable alternative warhead 17,18 although the addition of fluorine may prove to be detrimental to binding affinity. 18 Despite these challenges, the α-chloroacetamide derivatives remain of particular interest and are still included in screening campaigns along with their acrylamide counterparts where, in some cases, they prove to be superior. 14,17,[19][20][21][22] Chloroacetamide derivatives have also been identified to be some of the most potent GPx4 inhibitors (see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The acrylamide group is the most commonly used functional group in the resurgent field of targeted covalent inhibitors, by virtue of its inherent aqueous stability and limited off-target reactivity that enable effective design [30]. Indeed, judiciously designed TG2 inhibitors bearing an acrylamide warhead react nearly one billion-fold more rapidly with their target than with adventitious thiols, which greatly reduces the chance of off-target effects [31]. In AA9, the C-terminal dansyl group of NC9 is replaced by a naphthyl moiety, and the long, flexible polyethylene glycol linker of NC9 is substituted by a rigid piperazine core [32].…”
Section: Introductionmentioning
confidence: 99%
“…Initial estimates of k inact may also be inspired by values reported for a variety of similar warheads. 5 Alternatively, we have found that initial estimates of K I = 1 μM and k inact = 1 min −1 are appropriate for a broad range of irreversible inhibitors.…”
mentioning
confidence: 97%
“…2,3 The scaffold is designed to appropriately position the warhead at the site of reaction in an initial, non-covalent, reversible binding event to promote the subsequent irreversible reaction with the target without requiring the warhead to be highly intrinsically reactive. 4,5 These discoveries have led to a resurgence in the interest in TCIs, resulting in many clinical success stories. 3,6,7 However, methods for evaluating the efficiency of irreversible candidates are distinctly different than those traditionally applied to reversible inhibitors, since both binding affinity (K I ) and reactivity (k inact ) must be accounted for by time-dependent evaluation to give a complete picture of efficiency.…”
mentioning
confidence: 99%